(untitled) (Economia Aplicada, 2001)
Air pollution concentrations have been rapidly increasing in the major urban areas of Brazil caused mainly by the increasing use of vehicles. In response, mandatory emission standards were introduced by the Programa de Controle da Poluigao Veicular (Proconve) in 1988. This paper uses pollution emission and characteristics data to analyze the compliance of the automobile industry with pollution regulation during the 1992-1997 period. We find that the compliance trend adopted by manufacturers was not homogeneous. Larger automobiles had the fastest compliance schedule while popular models adjusted very slowly. Also gasoline-fueled models had a faster adjustment pattern than ethanol cars. We conclude that although the regulation was successful in reducing car emissions, no further regulation was established after 1997. Additional policies that could create incentives for selling cleaner automobiles and driving fewer miles should be introduced together with a coherent policy for providing alternative public transportation systems.